2009
DOI: 10.1111/j.1600-051x.2008.01372.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteraemia due to dental flossing

Abstract: Aims: The aims of this study were to (1) investigate the incidence of bacteraemia following flossing in subjects with chronic periodontitis or periodontal health; (2) identify the micro‐organisms in detected bacteraemias; and (3) identify any patient or clinical factors associated with such bacteraemia. Material and Methods: Baseline blood samples were obtained from 30 individuals with chronic periodontitis (17 M:13 F, 29–75 years) and 30 with periodontal health (17 M:13 F, 28–71 years) following a non‐invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
105
2
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 167 publications
5
105
2
7
Order By: Relevance
“…16,17 This especially happens during mastication 17 or daily oral hygiene measures. 18,19 Lockhart et al found bacteremia in 28% of individuals immediately after tooth brushing, and in 79% after tooth extraction. 19 It is therefore very likely that bacteremia occurs frequently in individuals with periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 This especially happens during mastication 17 or daily oral hygiene measures. 18,19 Lockhart et al found bacteremia in 28% of individuals immediately after tooth brushing, and in 79% after tooth extraction. 19 It is therefore very likely that bacteremia occurs frequently in individuals with periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is true that dental or other surgical procedures may cause bacteremia (16,29), routine daily events, such as mastication and tooth brushing, can also result in bacteremia as well (1,11,(19)(20)(21)29). It was estimated that the cumulative numbers of circulating bacteria (in CFU/ml/year) resulting from either mastication, tooth brushing two times daily or mere dental examination, were up to 5.6 million times, 154,000 times, and 48 times greater than that provoked by a single tooth extraction (14,32,42,43).…”
mentioning
confidence: 99%
“…9 However, the incidence of bacteraemia with flossing does not differ significantly between people with or without periodontal disease. 10 The incidence and magnitude of bacteraemia caused by flossing are the same as that caused by deep scaling/root planing within the same…”
Section: Introductionmentioning
confidence: 98%